Age of Sexual Debut and Cannabis Use in the United States. (20th March 2016) - Cha, Susan; Masho, Saba W.; Mezuk, Briana
ABSTRACT: Background: Understanding the interrelationships between risky health behaviors is critical for health promotion efforts. Conceptual frameworks for understanding substance misuse (e.g. stepping-stone models) have not yet widely incorporated other risky behaviors, including those related to sexual health. Objectives: The goals of this study were to assess the relationship between early sexual debut and cannabis use, examine the role of licit substance use in this association, and evaluate differences by gender and race/ethnicity. Methods: Data came from the National Comorbidity Survey-Replication (NCS-R). Primary analysis was restricted to respondents who reported sexual debut at ≥12 years ( n = 5, 036). Age at sexual debut was categorized as early (<18 years), average (18 years) and late (>18 years). Logistic regression was used to assess the relationship between age at sexual debut and cannabis use. Interaction terms were used to evaluate effect modification by gender and race/ethnicity. Results: Later age of sexual debut was associated with lower odds of cannabis use relative to the average age of debut (AOR = 0.50, 95% CI = 0.37–0.66). For every year that respondents delayed their sexual debut, the relative odds of lifetime cannabis use declined by 17%. After accounting for alcohol and tobacco use the association between early sexual debut and cannabis was attenuated (AOR = 0.90, 95% CI = 0.68–1.20), while later age of debut remained protective (AOR = 0.57, 95% CI = 0.42–0.78). Results were generally consistent across race/ethnicity and gender. Conclusions: Multifactorial intervention strategies targeting both sexual health and substance use may be warranted.